Advanced oxidation protein products, total thiol levels and total oxidant/antioxidant status in patients with nash - Başkol, Mevlut; Dolbun Seçkin, Kıymet; Başkol, Gülden (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: In this study we aim to evaluate the relationship of advanced oxidation protein products (AOPP), total thiol, total antioxidant status (TAS), total oxidant status (TOS) levels and oxidative stress index (OSI) in patients with nonalcoholic steatohepatitis (NASH). Materials and Methods: A total of 28 patients with NASH and 19 age-and-gender-matched healthy subjects were enrolled in the study as control group. Plasma AOPP and thiol levels were determined by spectrophotometric methods. Plasma TAS and TOS levels were measured using commercially available kits and OSI was calculated. Results: Plasma AOPP (256.7 vs. 125.8 μmol/L) and TOS levels (8.9 vs. 5.9 μmol H2O2 equiv/L) were higher in patients with NASH than the controls (p<0.019 and p<0.041 respectively). Plasma total thiol levels (235.0 vs. 291.6 μmol/L) were lower in patients with NASH than the controls (p<0.001). TAS levels (1.14 vs. 1.14 mmol Trolox equiv/L) were not significantly different in patients with NASH than the controls (p>0.900). OSI values (8.0 vs. 5.5) were higher in patients with NASH than the controls (p<0.039). Conclusion: Our findings indicate that oxidative stress increases in patients with NASH as shown by increases in TOS level. We think effective antioxidant therapy to inhibit protein oxidation and also to increase of TAS and total thiol levels may be a therapeutic option in patients with NASH who have under increased oxidative stress.